Redefining Work-Life Balance: The Transformative Power of Virtual HR Shared Services in the IT Industry - Harish, Bangalore Krishnamurthy (Digital Repository of Theses - SSBM Geneva, 2024)
This study investigates the impact of virtual HR shared services on work-life balance among IT professionals. We use methodologies such as descriptive studies, factor analysis, correlation analysis, multiple regression analysis, interaction effects study, and even structural modeling. The study seeks to investigate how these services affect employee satisfaction and retention rates, with a special emphasis on the IT sector. The findings imply an overall improvement in employee satisfaction and a reduction in churn rates as well as a major focus on virtual HR shared services. IT professionals exhibit the most improvements in both satisfaction and retention. However, the benefits were not uniform across all departments, highlighting need for tailored HR solutions. Correlation and regression analyses demonstrated a negative relationship between employee satisfaction and churn rates. The deployment of virtual HR shared services, salary rate, age, and department all had a major impact on these results. The interaction effects study highlighted the complexity of factors influencing HR outcomes, demonstrating that the combined influence of many variables such as department and special project counts has a significant impact on employee satisfaction and attrition rates We also deliver few insights into the relationships between insights and HR outcomes. It confirmed that virtual HR shared services positively impact employee satisfaction, which in turn reduces churn rates. These findings have various implications for human resource operations. Setting goals for virtual HR shared services for IT and related departments can improve employee retention and job satisfaction. Customizing HR solutions to match the specific demands of various departments is critical. Investing in user-friendly and effective HR solutions may speed up procedures and reduce administrative difficulties. Supporting remote work arrangements and continually improving HR services based on regular input from workers are also critical. Future study should include follow-up research to investigate the long-term impact of virtual HR shared services. Cross-industry assessments and research into certain HR technology and employee well-being initiatives can provide broader perspectives and improve understanding in this area. To summarize, virtual HR shared services dramatically improve work-life balance and lower attrition rates, particularly among IT workers. Organizations may promote a more pleased, engaged, and loyal staff by deploying adaptive, efficient, and specialized HR solutions, which helps them achieve their strategic goals and overall success.